The digital revolution: Lights and shadows: Lecture delivered at Fundación Ramón Areces - Roberto Serrano (Brown University, Department of Economics, 2019)
The digital revolution has brought about a wave of technological optimism, sustained by all the things technology does for us in our every day lives. This is in principle good, but it has a dark side, as the poor use of the new technologies may lead us to become lazier and to replace or strain rational processes of deliberation with the mechanical accumulation of numbers and data, which, allegedly, help objective and clear decision-making. This dark side produces a number of pathologies, which we could term 'digitalitis.' Manifestations of digitalitis include top5itis in the world of academic publishing, VAR-itis in the world of soccer, scooteritis in the world of means of transportation, or digital populism in democratic societies.
Keywords: A0; A1; O30; 330; digital revolution; digitalitis; top5itis; VAR-itis; scooteritis; digitalpopulism; regulation; education